PERAN GURU DALAM MENGEMBANGKAN KEMANDIRIAN ANAK USIA DINI DI SENTRA BAHAN ALAM (Penelitian Kualitatif pada Anak Usia 5-6 Tahun Kelas B di TK Negeri Pembina Cibeber Cilegon) - Selvi Apriliyani Sari; Fahmi; Rr. Dina Kusuma Wardhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Independence is an important aspect that needs to be developed in early childhood so that children are able to perform various activities on their own. This study aims to determine the role of teachers in developing independence in early childhood at the Natural Materials Center and to identify the forms of independence exhibited by 5–6-year-old children at Pembina Cibeber Cilegon Public Kindergarten. This study employed a descriptive qualitative method with 5–6-year-old children in Group B. Data collection techniques included observation, field notes, interviews, and documentation, with data analysis involving data reduction, data presentation, and drawing conclusions. The results indicate that children's independence developed well in the areas of discipline, intellectual development, and responsibility. The children began to be able to follow rules, solve simple problems, complete tasks, and tidy up their materials independently. Teachers served as facilitators, mentors, coaches, motivators, and role models who supported children's development of independence in their daily lives.